(untitled) (Vietnam Journal of Community Medicine, 2020)
The researchon 60 patients with lumber spinal disc herniation treated with physical therapy- rehabilitation methods at the hospital 198. The result as follows: Very good 30%, good 60%, average 10%. This is simple, non- pharmacological, conservative medical treatment that is effective for mild and moderate lumbar spinal disc herniation.